Hypertension measurement methods and differential diagnosis - Kaya, Bülent (Scientific Reports in Medicine, 2025)
Hypertension, a prevalent global health concern, significantly contributes to cardiovascular morbidity and mortality. Accurate diagnosis and management are essential to mitigate its complications. This review highlights the importance of various blood pressure (BP) measurement methods, including office BP (OBP), ambulatory BP monitoring (ABPM), and home BP monitoring (HBPM), emphasizing their roles in identifying conditions such as white coat hypertension (WCH) and masked hypertension (MH). ABPM and HBPM are preferred for their superior predictive value for target organ damage and cardiovascular risk compared to OBP. Central aortic BP (cBP) and arterial stiffness, assessed via pulse wave velocity (PWV), provide additional insights into vascular aging and cardiovascular risk. The review also explores subtypes of hypertension, including WCH, MH, nocturnal hypertension, and secondary hypertension, discussing their pathophysiology, clinical implications, and management strategies. Lifestyle modifications, such as dietary changes and exercise, remain pivotal in hypertension management, with the DASH diet and sodium restriction being particularly effective. Pharmacological interventions, including renin-angiotensin-aldosterone system inhibitors and SGLT2 inhibitors, demonstrate efficacy in BP control and cardiovascular risk reduction. Additionally, the impact of comorbid conditions like obstructive sleep apnea (OSA) and the role of antihypertensive therapies during COVID-19 are discussed. Emerging evidence underscores the need for individualized treatment approaches, incorporating advanced diagnostic tools and addressing modifiable risk factors. This comprehensive review aims to enhance understanding of hypertension’s complexities, guiding clinicians toward improved diagnostic accuracy and therapeutic outcomes.
Keywords: Hypertension; Blood pressure measurement; Central aortic blood pressure